Tree arrangements for silvopastoral system: livestock advisors’ knowledge and attitudes - De-Sousa, Karolini Tenffen; Deniz, Matheus [UNESP]; Hill, João Ari Gualberto; Dittrich, João Ricardo; Hötzel, Maria José (Springer Nature, 2023)
The choice of tree arrangement can determine the success or failure of a silvopastoral system. We explored the knowledge and attitudes of livestock advisors regarding different tree arrangements and their perception of the benefits of the system to the pasture and the animals. Advisors from southern Brazil (n = 228) participated in an online survey. A short definition of silvopastoral systems and a schematic representation of five tree arrangements (single-row, tree-row on the border fence, multiples-rows, woodland and scattered trees) were presented, followed by open-ended, multiple-choice, and 5-point Likert scale questions. Participants were more likely to be male (84%), agronomists (47%), and 40% were older than 51 years old. Only 29% of participants stated to be acquainted with all the tree arrangements. Participants had more positive attitude toward single-row than the other tree arrangements and recognize the single-row as the most suitable from an ecological, economical and animal welfare point of view. Woodland and scattered trees arrangements were perceived as less economically viable than the others. Participants perceived the silvopastoral system beneficial to the welfare of the animals (99%), and to the pasture (62%). The main benefit mentioned for the animals and the pasture was the improvement of the microclimate, given the protection of animals from heat and the pasture from frost. In conclusion, the participants had positive attitudes towards the silvopastoral systems and their potential benefits to pasture and to animals. Also, they had more positive attitude to the tree arrangements with which they were most familiar, i.e., single-row, border fence, and multiple-row.
Keywords: Advice; Expertise; Rural extension; Silvopastoral design; Thermal comfort; Welfare